Implication of long non-coding RNAs in the pathophysiology of cardiac rejection and its accuracy in diagnosis. (3rd October 2022) - Perez-Carrillo, L; Gimenez-Escamilla, I; Trivino, J C; Martinez-Dolz, L; Portoles, M; Tarazon, E; Rosello-Lleti, E
Abstract: Background: The complementation of the endomyocardial biopsy or even its replacement by the use of a non-invasive method is one of the great challenges in the investigation of cardiac rejection. However, the limitations of the serum markers identified so far limit their use in clinical practice. In recent years, many long non-coding RNAs (lncRNAs) have been identified along with their role in different biological functions. However, the utility of lncRNAs in cardiac rejection has not been explored. Purpose: We aimed to determine the expression of lncRNAs in serum of patient with cardiac rejection and evaluate the diagnostic capacity as potential biomarkers for the non-invasive detection of mild (grade 1R) or moderate/severe (grade ≥2R) cellular rejection. Methods: RNA sequencing analysis (Illumina HiSeq 2500) was performed on forty serum samples from transplant recipients undergoing routine endomyocardial biopsies. Twenty eight samples were diagnosed with RCA (RCA Grade 1R, n=16; and RCA Grade ≥2R, n=12) and 12 samples had no diagnosed rejection. Results: Of the 10, 144 lncRNAs detected in serum, 5.1% presented differential expression in patients with cardiac rejection of Grade ≥2R. Fifty-six molecules showed excellent diagnostic ability in moderate-severe rejection (AUC >0.900) and fifty-one molecule were even able to detect mild rejection with good diagnostic ability for moderate-severe rejection (AUC >0.800). Three lncRNAs stand out: EGFR-AS1 (≥2R, AUC=0.871, p<0.01; 1R, AUC=0.921, p<0.0001), AC008649.2 (≥2R, AUC=0.867, p<0.01; 1R, AUC=0.807, p<0.01) and AP001652.1 (≥2R, AUC=0.848, p<0.01; 1R, AUC=0.855, p<0.01). Conclusions: A large number of lncRNAs with excellent diagnostic capacity for acute cellular rejection have been identified. In addition, we highlight 3 long non-coding (EGFR-AS1, AC008649.2 and AP001652.1) that maintain a good diagnostic capacity even in the mildest degrees. Therefore, we propose these non-coding RNAs as potential biomarkers of cardiac rejection. Although the function of these non-coding RNAs in acute cellular rejection is unknown, it is important to take into account in future studies the pathways in which they participate in order to elucidate the mechanisms involved in the development of this pathology. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Health Carlos III European Regional Development Fund (ERDF)